How to fly (in ten thousand easy lessons) eaudiobook Poetry. - Kingsolver, Barbara (2020)
""A gorgeous collection. . . . These poems unplug from TV and social media and the outrage of the moment and turn our attention to the immediate and the everlasting, human intimacy and the power and mystery of nature."" — Tampa Bay Times In this intimate collection, Barbara Kingsolver, beloved author of The Poisonwood Bible and the Pulitzer Prize-winning Demon Copperhead, and recipient of numerous literary awards including the National Book Foundation's Medal for Distinguish Contribution to American Letters, trains her eye on the everyday and the metaphysical in poems that are beautifully crafted, emotionally rich, and luminous In her second poetry collection, Kingsolver offers reflections on the practical, the spiritual, and the wild. She begins with "how to" poems addressing everyday matters such as being hopeful, married, divorced; shearing a sheep; praying to unreliable gods; doing nothing at all; and of course, flying. Next come rafts of poems about making peace (or not) with the complicated bonds of friendship and family, and making peace (or not) with death, in the many ways it finds us. Some poems reflect on the redemptive powers of art and poetry itself; others consider where everything begins. Closing the book are poems that celebrate natural wonders—birdsong and ghost-flowers, ruthless ants, clever shellfish, coral reefs, deadly deserts, and thousand-year-old beech trees—all speaking to the daring project of belonging to an untamed world beyond ourselves. Altogether, these are poems about transcendence: finding breath and lightness in life and the everyday acts of living. It's all terribly easy and, as the title suggests, not entirely possible. Or at least, it is never quite finished. Supplemental enhancement PDF accompanies the audiobook.